2019
DOI: 10.1017/s0022029919000700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a pre-milking teat foam and a liner disinfectant on the presence of mesophilic and (proteolytic) psychrotrophic bacteria prior to milking

Abstract: Contamination of raw milk by psychrotrophs can lead to the production of heat-resistant proteases and subsequent spoilage of UHT milk. Therefore, this research communication evaluated the effect of a pre-milking teat disinfectant (active components: L-(+)-lactic acid and salicylic acid) and a liner disinfectant (active components: peracetic acid and hydrogen peroxide) on the number of mesophilic and (proteolytic) psychrotrophic bacteria prior to milking. The teat orifices of 10 cows were sampled using a swabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Furthermore, the Source Tracker analysis indicated that the microbes identified from the teat liner had a significant correlation with the microbes identified in milk samples at Zhengzhou farm. The results were consistent with a previous study of psychrotrophic bacteria from teat liners, where liner disinfection did not result in a significant reduction in the number of target bacteria [33]. The presence of contamination suggests a possible scenario that the sanitizing procedures are not effective in neutralizing microbiota or there might be a secondary contamination.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the Source Tracker analysis indicated that the microbes identified from the teat liner had a significant correlation with the microbes identified in milk samples at Zhengzhou farm. The results were consistent with a previous study of psychrotrophic bacteria from teat liners, where liner disinfection did not result in a significant reduction in the number of target bacteria [33]. The presence of contamination suggests a possible scenario that the sanitizing procedures are not effective in neutralizing microbiota or there might be a secondary contamination.…”
Section: Discussionsupporting
confidence: 91%
“…The left breast of each cow was bathed with PHMB teat disinfectant, whereas the right breast was treated with a PHMB solution (3 g/L) for the control group. The cow's teat was fully immersed in disinfectant for 15 s with a teat pre-dip foam [36]. At 10 min and 12 h after disinfection, a sterile cotton rod dipped in neutralizer was used to collect samples from three different positions on the outer side of the breast.…”
Section: Teat Swabbing Proceduresmentioning
confidence: 99%